Drug-Induced Fatty Liver Disease - A. P. Pereverzev; O. D. Ostroumova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Drug-induced fatty liver disease (DIFLD) covers a group of adverse drug reactions whose prevalence accounts for about 10% of all adverse reactions. The aim of this review was to analyse and summarise data on medicines that can potentially lead to the development of DIFLD, as well as on the pathophysiological mechanisms of its development, methods of its diagnosis, treatment, and prevention. The analysis of scientifi c literature showed that most often this complication occurred following the use of amiodarone, methotrexate, tamoxifen, valproic acid, and some other medicines. It was demonstrated that the main risk factors for developing DIFLD are comorbidity/polymorbidity and mitochondrial dysfunction. Due to the lack of pathognomonic clinical manifestations of DIFLD the best approach to making diagnosis is to obtain a thorough medical history, including medication history, to use RUCAM and Naranjo scales, to analyse a number of blood chemistry parameters (alanine transaminase, aspartate transaminase, bilirubin, alkaline phosphatase), and, if necessary, to perform liver biopsy. Whenever DIFLD is observed in a patient, it is necessary, if possible, to discontinue the use of the medicine that caused the adverse reaction, or to lower its dose and to exclude the factors that may potentially aff ect the patient's condition. The following measures will help healthcare professionals to prevent and detect DIFLD in a timely manner: observing the requirements of the patient information leafl et, taking into account any comorbidity and potential adverse drug interactions, as well as regular monitoring of the condition of patients taking medicines with known hepatotoxic eff ects.